Wide-field mosaics of the corneal subbasal nerve plexus in Parkinson’s disease using in vivo confocal microscopy - Reza A. Badian (Nature Portfolio, 2021)
Measurement(s) Prominent corneal nerve fibers • Dendritic Cell Technology Type(s) confocal microscopy Factor Type(s) disease status • comorbidity Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.16691452